The Intensive Language Teaching Program in Teaching Arabic Language to The Islamic Center Group “Abdullah Ghanem Al-Shamael” Ponorogo Held at the Darussalam Gontor University - Yoke Suryadarma; Ahmad Muthi Baiquni (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
This research is the implementation of the intensive language program in the teaching of the Arabic language of the Islamic Center Group